2019
DOI: 10.1002/lary.27893
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic radiographic sinonasal inflammation does not affect pituitary surgery outcomes

Abstract: Objective: Chronic rhinosinusitis (CRS) is a proposed risk factor for meningitis and other intracranial complications following the endoscopic endonasal transsphenoidal approach (TSA). Some have recommended staging TSA following surgery for CRS; however, delaying TSA has important ramifications. The objective of this study is to determine whether asymptomatic sinonasal inflammation (RSNI) on preoperative computed tomography scans, without clinical CRS, is associated with postoperative complications following T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…4,[18][19][20] Sphenoiditis was recently reported as a risk factor, although several studies have stated that RS is not related to postoperative CNS infection. 3,4,[20][21][22] Prophylactic management has been recommended before TS surgery, being classified as a clean-contaminated procedure due to the air-containing sphenoid sinus. 23) Schaberg, et al 18) reported that seven patients with preoperative sphenoiditis underwent concurrent ESS and endoscopic surgery of the anterior skull base; no postoperative intracranial complications were noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,[18][19][20] Sphenoiditis was recently reported as a risk factor, although several studies have stated that RS is not related to postoperative CNS infection. 3,4,[20][21][22] Prophylactic management has been recommended before TS surgery, being classified as a clean-contaminated procedure due to the air-containing sphenoid sinus. 23) Schaberg, et al 18) reported that seven patients with preoperative sphenoiditis underwent concurrent ESS and endoscopic surgery of the anterior skull base; no postoperative intracranial complications were noted.…”
Section: Discussionmentioning
confidence: 99%
“…8) Thus, controlling RS before performing TS surgery was strongly recommended, but the delay to surgery resulted in further deterioration of neurologic condition, manifested in vision changes, headache, and abnormal endocrine function. 3,9) We previously reported the operative outcomes of concurrent treatment of pituitary adenoma and chronic RS; the work was preliminary in nature. Postoperatively, no increase in the extent of RS was seen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of patients with skull base pathology requiring operative intervention with concomitant chronic rhinosinusitis findings on imaging remains controversial. While some authors recommend addressing the sinonasal disease at the time of ESBS, [5][6][7][8] others have advised against this due to the risk of intracranial spread of infection, particularly in the presence of sphenoid sinus disease. [9][10][11][12][13] Encountering an unexpected active infection may also result in the need for same day cancellation of an ESBS, which can be very disruptive for the patient, the surgeon, and the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that preexisting asymptomatic radiographic sinonasal disease, assessed via Lund-Mackay score on computer tomography (CT), does not increase risk for postoperative complications including PRS. 9 The risk associated with preoperative endoscopic findings and patient-reported symptoms have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%